A cross-sectional study on the physical and mental health condition of university newcomers in Bangladesh - Arpita Roy; Sadia Amrin; Md. Ashraful Alam; Hafsa Akter; Sadhon Kumar Ray; Md. Momin Islam; Munawar Sultana (Discover Mental Health)
Abstract In Bangladesh, an extensive enrollment examination is required to enroll in different universities, where students from all 64 districts of Bangladesh compete to get a place. Students either migrate from their home districts to another place or continue from home if they reside in the same city. However, it is undeniable that there is a huge and sudden change in the lifestyle of the newly enrolled students. This study was conducted on 50 universities in Bangladesh to investigate the overall health conditions of the university newcomers (N = 605) in six academic sessions from 2016 to 2022. The study showed that more than half of the students (52.6%) became physically sick after admission. The majority (81.5%) of the respondents felt mental pressure, and the maximum (83.3%) were concerned about their mental health condition, which is often unnoticed for this group of students. This also highlighted that during COVID-19, participants’ mental health deteriorated drastically (71.7%). Nevertheless, the medical centers of the respective institutions were completely heedless in the majority (79.3%) of cases. Lastly, the respondents themselves tried to provide appropriate suggestions that will be helpful for the future well-being management of the newcomers. Thus, unveiling the overall health condition of newcomers is necessary so that every respective individual becomes aware of the condition and the current situation changes into a student-friendly and lively environment. To our knowledge, this is one of the first kinds of investigation in Bangladesh.